Long‐range projections from sparse populations of GABAergic neurons in murine subplate - Boon, Jacqueline (J Comp Neurol, 2019)
The murine subplate contains some of the earliest generated populations of neurons in the cerebral cortex, which play an important role in the maturation of cortical inhibition. Here we present multiple lines of evidence, that the subplate itself is only very sparsely populated with GABAergic neurons at postnatal day (P)8. We used three different transgenic mouse lines, each of which labels a subset of GABAergic, ganglionic eminence derived neurons. Dlx5/6‐eGFP labels the most neurons in cortex (on average 11% of NEUN+ cells across all layers at P8) whereas CGE‐derived Lhx6‐Cre::Dlx1‐Venus(fl) cells are the sparsest (2% of NEUN+ cells across all layers at P8). There is significant variability in the layer distribution of labeled interneurons, with Dlx5/6‐eGFP and Lhx6‐Cre::R26R‐YFP being expressed most abundantly in Layer 5, whereas CGE‐derived Lhx6‐Cre::Dlx1‐Venus(fl) cells are least abundant in that layer. All three lines label at most 3% of NEUN+ neurons in the subplate, in contrast to L5, in which up to 30% of neurons are GFP+ in Dlx5/6‐eGFP. We assessed all three GABAergic populations for expression of the subplate neuron marker connective tissue growth factor (CTGF). CTGF labels up to two‐thirds of NEUN+ cells in the subplate, but was never found to colocalize with labeled GABAergic neurons in any of the three transgenic strains. Despite the GABAergic neuronal population in the subplate being sparse, long‐distance axonal connection tracing with carbocyanine dyes revealed that some Gad65‐GFP+ subplate cells form long‐range axonal projections to the internal capsule or callosum.